Concomitant chemoradiotherapy with low-dose weekly gemcitabine for nonmetastatic unresectable pancreatic cancer - Beste Melek ATASOY,; Faysal DANE,; Ayşegül ÜÇÜNCÜ KEFELİ,; Hale ÇAĞLAR,; Asım CİNGİ,; Nazım Serdar TURHAL,; Ufuk ABACIOĞLU,; Cumhur YEĞEN, (Turkish Journal of Gastroenterology, 2019)
-